Cooperative Learning Model: Learning Solutions for Slow Learner Students in Elementary Schools - Mohd Fakhruddin, Fathiyah; Yulia Citra, Rini; Yulia, Rina; Sutarto, Sutarto; Minsih, Minsih (Sekolah Tinggi Agama Islam Solok Nan Indah, 2024)
The phenomenon of teacher-centered learning activities, limited availability of media and supporting tools, and the existence of students who have slow understanding abilities in learning (Slow Learners) are one of the bases for this research. The aim of this research is to determine and describe the planning, implementation and improvement of Islamic Religious Education learning outcomes for Slow Learner students using the Cooperative Learning model. This type of research is Classroom Action Research which was carried out at a school in Indonesia. The research subject was a teacher with twenty students. Data collection techniques used were observation and tests. All data was analyzed using descriptive quantitative analysis, so that a conclusion was obtained about improving learning outcomes using the cooperative learning model. This research found that the use of a cooperative learning model with careful planning and good implementation can increase students' learning completeness.